Critical focus on mechanisms of resistance and toxicity of m-TOR inhibitors in pancreatic neuroendocrine tumors. (June 2017) - Antonuzzo, L.; Del Re, M.; Barucca, V.; Spada, F.; Meoni, G.; Restante, G.; Danesi, R.; Di Costanzo, F.; Fazio, N.
Highlights: Everolimus prolonged PFS in pNETs, but the onset of drug resistance results in disease progression. PI3K/mTOR dual inhibitors overcome primary and acquired resistance in pre-clinical models. BEZ-235 showed an exciting activity in preclinical models but failed in clinical trials. The knowledge of the pathogenesis of adverse events is critical to prevent severe toxicities. Abstract: Pancreatic neuroendocrine tumors (pNETs) are rare neoplasms representing less than 2% of all pancreatic malignancies. The PI3K-AKT-mTOR pathway is often deregulated in pNETs and seems to play a key role in tumorigenesis. Everolimus, an inhibitor of the mTOR pathway, has demonstrated efficacy in the treatment of pNETs. Nevertheless de novo or acquired drug resistance is responsible for disease progression and represents a major obstacle to overcome by clinicians. Blocking the PI3K/AKT/mTOR pathway may cover the supposed main mechanisms of resistance to everolimus. Therefore, BEZ-235, a potent oral dual PI3K/mTOR inhibitor was investigated in clinical trials. Globally more than 250 patients with different types of solid tumors were treated. Two studies were conducted in pNETs with BEZ-235 as single agent. The former was a phase 2 trial conducted in pNETs resistant to everolimus while the latter a randomized trial comparing everolimus and BEZ-235. Unfortunately, both the studies disappointed the expectations and were prematurely halted mainly due to severe toxicity. On this basis we reviewed m-TOR inhibitors in pNETs, focusing on their mechanisms of resistance and toxicity.